Chemical Constituents and Biological Activities From Garcinia Maingayi and Garcinia Parvifolia - Lin, Cheow Yuen (2005)

(untitled)
In this present study, the stem bark of Garcinia maingayi and Garcinia parvifolia were investigated and resulted in the isolation of nine compounds. There are no previous reports on chemical components and biological activities from Garcinia maingayi. The structures of these compounds were elucidated by using spectroscopic experiments namely NMR, MS, IR and UV. Being the first report on Garcinia maingayi, detailed chemical studies have afforded two triterpenoids, stigmasterol and sitosterol, two xanthones, 1,3,7-trihydroxy-2-(3- methylbut-2-enyl)-xanthone and 1,3,6,8-tetrahydroxyxanthone, one benzophenone, isoxanthochymol, and one benzoic acid derivative methyl 3,4-dihydroxybenzoate. The findings are significant as it contributes to the knowledge of the chemotaxonomy on Garcinia species and all these compounds are new to the species. iii Meanwhile investigations on Garcinia parvifolia have afforded one triterpenoid, α- amyrin and two xanthones, cowanin and rubraxanthone. Acetylation reaction was carried out on rubraxanthone to yield triacetate rubraxanthone. This is also the first report on cytotoxic and larvicidal activities of Garcinia maingayi, Garcinia parvifolia and rubraxanthone. Cytotoxic tests were performed using HL-60 and CEM-SS cell lines. The crude hexane and chloroform extracts of Garcinia maingayi were active against HL-60 cell line with IC50 values of less than 30 μg/ml. The crude hexane and acetone extracts of Garcinia parvifolia were found to be active against CEM-SS cell line with IC50 values of less than 30 μg/ml meanwhile, the crude chloroform extract gave a significant activity with an IC50 value of 6.5 μg/ml. The antimicrobial assay was carried out against four pathogenic bacteria, Methicillin resistant Staphylococcus aures, Pseudomonas aeruginosa, Staphylococcus typhimurium and Bacillus subtilis. Most of the crude extracts tested against these microbes gave only moderate or weak activity. The antifungal activity testing of the plant extracts were carried out against the fungi Candida albican, Aspergillus ochraceaus, Sacchoromyces cerevisiae and Candida lypolytica. No activity was observed for all the crude extracts The larvicidal test was carried out towards the larvae of Aedes aegypti. All the crude extracts of Garcinia maingayi were weakly active against the larvae with LC50 values of more than 150 μg/ml. The crude extracts of Garcinia parvifolia showed moderate activities against the larvae by giving LC50 values of less than 100 μg/ml. The pure iv rubraxanthone showed a strong activity against the larvae with a LC50 value of 15.49 μg/ml.